Dual PI3Kδ/γ Inhibitor Duvelisib Prevents Development of Neuropathic Pain in Model of Paclitaxel-Induced Peripheral Neuropathy - Adamek, Pavel; Heles, Mario; Bhattacharyya, Anirban; Pontearso, Monica; Slepicka, Jakub; Palecek, Jiri (The Journal of neuroscience, 2022)
The development of painful paclitaxel-induced peripheral neuropathy (PIPN) represents a major dose-limiting side effect of paclitaxel chemotherapy. Here we report a promising effect of duvelisib (Copiktra), a novel FDA-approved PI3Kδ/γ isoform-specific inhibitor, in preventing paclitaxel-induced pain-like behavior and pronociceptive signaling in DRGs and spinal cord dorsal horn (SCDH) in rat and mouse model of PIPN. Duvelisib blocked the development of mechanical hyperalgesia in both males and females. Moreover, duvelisib prevented paclitaxel-induced sensitization of TRPV1 receptors, and increased PI3K/Akt signaling in small-diameter DRG neurons and an increase of CD68+ cells within DRGs. Specific optogenetic stimulation of inhibitory neurons combined with patch-clamp recording revealed that duvelisib inhibited paclitaxel-induced weakening of inhibitory, mainly glycinergic control on SCDH excitatory neurons. Enhanced excitatory and reduced inhibitory neurotransmission in the SCDH following PIPN was also alleviated by duvelisib application. In summary, duvelisib showed a promising ability to prevent neuropathic pain in PIPN. The potential use of our findings in human medicine may be augmented by the fact that duvelisib is an FDA-approved drug with known side effects.SIGNIFICANCE STATEMENT We show that duvelisib, a novel FDA-approved PI3Kδ/γ isoform-specific inhibitor, prevents the development of paclitaxel-induced pain-like behavior in males and females and prevents pronociceptive signaling in DRGs and spinal cord dorsal horn in rat and mouse model of paclitaxel-induced peripheral neuropathy.
Keywords: fosfatidylinositol-3-kinasy; Purines; Male; Antineoplastic Agents, Phytogenic; Hyperalgesia; Neuralgia; Pain; puriny; mužské pohlaví; Phosphatidylinositol 3-Kinases; paclitaxel; Peripheral Nervous System Diseases; Paclitaxel; krysa rodu Rattus; bolest; Animals; ženské pohlaví; isochinoliny; zvířata; Rats; nemoci periferního nervového systému; myši; Isoquinolines; Mice; fytogenní protinádorové látky; Female; hyperalgezie; neuralgie